Pengembangan Media Destinasi Pariwisata: Memanfaatkan Potensi dan Sumber Daya Lokal di Era Otonomi dan Pemekaran Daerah - Yosafati Hulu (Bina Nusantara University, 2012)
Concerning about: (1) an increase in regional demand (government and community) in developing tourism destinations in the era of autonomy and separation, (2) the needs of tourists to choose the right attraction in accordance with their respective criteria, and (3) the needs of employers to offer sights of interest in accordance with the needs of potential tourists, a media is needed to be developed that can facilitate those needs. It is a web-based software system that can store and show tourist destinations of Indonesia in a comprehensive, systematic, and structured way. Besides, it can classify the various attractions based on attributes, such as: location (name of the island, province, district), tourism type/product, how to go to thoseobjects, cost, and also another variety of informal information, such as: the ins and outs of the attraction area posted by the local community or travel experiences posted by tourists. The first phase will focus on a database system that enables local governments and local communities retain information attractions and products systematically and structurally so that potential tourists can find them easily through a simple search method. The database system is then a basis og other information that will be built on further research needs such as:Data Warehouse System, Decision Support System, and Expert System for Indonesia's tourism industry.